2012
DOI: 10.1590/s0004-282x2012000900003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and treatment with botulinum toxin in blepharospasm: a 17-year experience

Abstract: OBJECTIVE: It was to analyze clinical aspects of patients with blepharospasm, including outcomes of botulinum toxin treatment. Additionally, clinical characteristics of isolated blepharospasm were compared to those of blepharospasm plus other movement disorders. METHODS: Clinical data recorded during 17 years were reviewed. The variables included age, gender, age of onset, past medical history, head trauma, smoking history, family history of dystonia, severity, duration of botulinum toxin relief and adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…of pretarsal injections (15.4%) than in the Gil-Polo study (41.2%). 22 Additionally, the results of our study are consistent with many of those previously published with shorter follow-up periods [22][23][24][25] regarding not only the efficacy of the BTA but also the epidemiological findings (age at onset and female predominance).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…of pretarsal injections (15.4%) than in the Gil-Polo study (41.2%). 22 Additionally, the results of our study are consistent with many of those previously published with shorter follow-up periods [22][23][24][25] regarding not only the efficacy of the BTA but also the epidemiological findings (age at onset and female predominance).…”
Section: Discussionsupporting
confidence: 90%
“…This study found an incidence of adverse events of the 8.3% in patients with BPS. In line with these results, Aquino et al 25 reported an incidence of adverse events of the 14% in a cohort of 113 patients treated Figure 1. Patient Evaluation of Global Response Scale.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Of the 101 patients, 78 (77.2%) were women and the mean age was 64.9 years. Aquino et al [17] identified 125 patients (75% women) after evaluating their 17-year clinical data. The mean age was 54.3 years, and the mean duration of the effect of the toxin was 3.1 months.…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
“…Aquino et al 40 (level III) retrospectively studied 125 patients with BEB over a 17-year span to evaluate the clinical features and therapeutic outcomes of Botox and Dysport. However, the authors reported on efficacy of botulinum toxin overall, without a separate analysis of the Botox and Dysport outcomes.…”
Section: Onabotulinumtoxina (Botox)mentioning
confidence: 99%